Unravelling the enigma of ligninOX: can the oxidation of lignin be controlled?. Issue 3 (23rd November 2017) - Guo, Haiwei; Miles-Barrett, Daniel M.; Neal, Andrew R.; Zhang, Tao; Li, Changzhi; Westwood, Nicholas J.
Abstract : As societal challenges go, the development of efficient biorefineries as a means of reducing our dependence on petroleum refineries is high on the list. Abstract : As societal challenges go, the development of efficient biorefineries as a means of reducing our dependence on petroleum refineries is high on the list. One of the core strengths of the petroleum refinery is its ability to produce a huge range of different products using all of the components of the starting material. In contrast, the target of using all the biopolymers present in lignocellulosic biomass is far from realised. Even though our ability to use the carbohydrate-based components has advanced, our plans for lignin lag behind (with the notable exception of vanillin production). One approach to lignin usage is its controlled depolymerisation. This study focuses on an increasingly popular approach to this challenge which involves highly selective lignin oxidation to give a material often referred to as lignin OX . But what do we mean by lignin OX ? In this study we show that it is possible to form many different types of lignin OX depending on the oxidation conditions that are used. We show that variations in the levels of processing of the β–O-4, the β–β and a third linkage occur. Through use of this information, we can form a well-defined lignin OX from six different hardwood lignins. This process is reproducible and can be carried out on a large scale. With a source of well-defined lignin OX in hand, we show that it can be converted to simple aromatic monomers and that any remaining lignin OX is sufficiently soluble for further processing to be carried out.